2013
DOI: 10.1016/j.nutres.2013.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Exercise prevents hyperhomocysteinemia in a dietary folate-restricted mouse model

Abstract: Hyperhomocysteinemia is a condition that results from altered methyl group metabolism and is associated with numerous pathological conditions. A number of nutritional and hormonal factors have been shown to influence circulating homocysteine concentrations; however, the impact of exercise on homocysteine and methyl group balance is not well understood. Our hypothesis was that exercise represents an effective means to prevent hyperhomocysteinemia in a folate-independent manner. The purpose of this study was to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 54 publications
(63 reference statements)
1
28
0
Order By: Relevance
“…The findings that exercise reverses the effects of HHcy on skeletal muscle dysfunction agree with other studies that exercise decreases or prevents increases in plasma Hcy levels (Neuman et al, 2013;Randeva et al, 2002).…”
Section: Hhcy Promotes Inflammation In Cbs+/-skeletal Musclesupporting
confidence: 90%
See 4 more Smart Citations
“…The findings that exercise reverses the effects of HHcy on skeletal muscle dysfunction agree with other studies that exercise decreases or prevents increases in plasma Hcy levels (Neuman et al, 2013;Randeva et al, 2002).…”
Section: Hhcy Promotes Inflammation In Cbs+/-skeletal Musclesupporting
confidence: 90%
“…It has been demonstrated that exercise is capable of lowering Hcy levels, suggesting that exercise can potentially negate the adverse effects of HHcy on different organs (Hrncic et al, 2013;König et al, 2003;Neuman et al, 2013;Randeva et al, 2002;Vincent et al, 2006). Neuman et al stated that exercise was capable of preventing increases in plasma Hcy concentration that were produced by 7 weeks of a folate restricted diet in mouse models (Neuman et al, 2013).…”
Section: Exercise and Homocysteinementioning
confidence: 99%
See 3 more Smart Citations